Prevalence of Endocrine Complications in Transfusion-Dependent Beta Thalassemic Pakistani Patients - Fatima, Itrat; Yaqub, Naila; Anwar, Tazeen; Nisar, Yasir Bin; Khalid, Sadaf; Gilani, Sara (International Journal of Pathology, 2018)
Objectives: To investigate the frequency of endocrine complications among β-thalassemic patients in Pakistan.Materials and Methods: The current cross sectional study was conducted at the Thalassemia Centre, Islamabad,Pakistan between October 2013 and March 2014. We enrolled 96 β-thalassemic patients and blood samples weredrawn to determine serum calcium, phosphate, ferritin, parathyroid hormone, free T4, thyroid stimulating hormone,25-hydroxy vitamin D and random blood sugar levels. Comparison of demographic features and serum ferritinlevels between patients with endocrine and without endocrine complication was done using logistic regressionanalysis and odds ratio (OR), 95% confidence interval (CI) and p-values were reported. The level of significantwas considered at 5%.Results: Out of 96, 56 (58.3%) were male patients. The mean (±SD) age and ferritin levels of patients was 13.8(±3.8) years and 4447 (±2945) ng/mL, respectively. Out of 96, 40 (41.7%) patients had endocrine complications –hypoparathyroidism (24.0%), hypothyroidism (13.5%), vitamin D deficiency (3.1%) and diabetes (1.1%). Thalassemicpatients who had higher serum ferritin levels (3000 ng/ml or more) had significantly higher odds of endocrinecomplications (OR 5.42, p=0.038) compared to those who had low serum ferritin levels (<1500 ng/ml) adjustedfor age and gender.Conclusions: Slightly over two-fifths of β-thalassemic patients had endocrine complication. A quarter of patientshad hypoparathyroidism, while one in seven patients had hypothyroidism. A strong association between the endocrinecomplications and a high serum ferritin level was found in our study population. Hypogonadism is picked atpubertal age group, and Diabetes occurs in second decade and our selected group was mostly prepubertal.